2010
DOI: 10.1049/iet-rpg.2009.0134
|View full text |Cite
|
Sign up to set email alerts
|

Integration of large-size photovoltaic systems into the distribution grids: a P–Q chart approach to assess reactive support capability

Abstract: This study addresses the issue of the control of both active (P) and reactive (Q) power flows injected by grid connected photovoltaic (PV) units participating in the provision of the reactive power compensation ancillary service. A model is derived allowing to define a sort of 'capability chart' for the PV unit, that is, the set of points in the P-Q plane which, at steady state, can be reached by properly operating the control system and without exceeding the physical limits of all the involved devices. To thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…It should be observed that, if one wants to account also for the converter losses, an empirical correction to the resistances R and R T can be done without affecting the procedure (see [34] for details). The power P s0 can be expressed as: (16) and, if one inserts Equation (6) into Equation (5) and Equation (5) into Equation (9) and nullifies all the time derivatives (to account for the steady-state condition), it is possible to write the following steady state equations:…”
Section: Machine Side Portionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be observed that, if one wants to account also for the converter losses, an empirical correction to the resistances R and R T can be done without affecting the procedure (see [34] for details). The power P s0 can be expressed as: (16) and, if one inserts Equation (6) into Equation (5) and Equation (5) into Equation (9) and nullifies all the time derivatives (to account for the steady-state condition), it is possible to write the following steady state equations:…”
Section: Machine Side Portionmentioning
confidence: 99%
“…• Type I: the MPPT curve input is the actual turbine speed and produces the reference signal for the power to be produced by the PMSG [24][25][26][30][31][32][33][34] (see Figure 5). Nevertheless, in both Type I and Type II configurations, the system is obliged to work at a point whereby the active power P s produced by the PMSG follows the MPPT curve, which is not feasible, unless one neglects the losses in the electric machine.…”
mentioning
confidence: 99%
“…Solar photovoltaic (PV) power is a commercially available and reliable technology with a significant potential for long-term growth [1][2][3][4][5][6][7][8][9][10][11][12][13]. A possible location for PV panels is in residential areas where they form a low-voltage (LV) distribution grid.…”
Section: Introductionmentioning
confidence: 99%
“…Inverter control strategy was proposed to allow DGs to support grid voltage during voltage sags in [16]. The limitation of maximum available active and reactive power of PV systems was evaluated in [17]. In [18], the adaptive zoning technique was proposed to recover the grid voltage within allowable limits after disturbances.…”
Section: Introductionmentioning
confidence: 99%